The dolina - Sauro, Ugo (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
Professor Ivan Gams' research has given an important contribution to the study of the karst dolines. He described how the dolines began to develop as hidden forms before emerging as visible forms. The most common dolines are the result of the "accelerated corrosion" of the soluble rock in the central part of the depressions. From the study of the karst dolines it is possible to distinguish many types of form resulting from different genetical mechanisms. The characters of the populations of the dolines of seven rock-cutterraces on the Montello Plateau allow us to formulate a preliminary model for the evolution of the forms. In the Classical Karst it is easy to recognize how different sub-populations may coexist in the same area as a result of alternating favorable and unfavorable climatic environments.
Keywords: geomorfologija; geomorphology; kras (geologija); kraške oblike; morfogeneza; vrtače